Inovasi dalam Lembaga Pendidikan - Putri, Rizky Ananda; Khoriroh, Fitri; Zohriah, Anis; Firdaos, Rijal (Jurnal Ilmiah Wahana Pendidikan, 2025)
Educational innovation is an effort to overcome existing challenges in education. Innovation in the educational context can take the form of various things, be it products or systems. For example, a teacher can create learning media in the form of mock ups to improve the quality of learning. The educational innovation model at the Indonesian Ministry of Education and Culture still tends to use a "top-down" strategy, where educational innovation is developed from central policy to the lowest educational institutions in an imperative way. This can hamper the creativity of teaching and education staff. Therefore, a balance is needed with a "bottom-up" strategy, where educational innovation is developed from below, originating from the creativity of teaching and education staff in each educational institution, as an effort to improve the quality of education delivery.